The impact of screen time on children’s well-being development: a scoping review - Mee, Rita Wong Mee; Harun, Noor Hanim; Pek, Lim Seong; Mohamed, Suzulaikha; Shahdan, Tengku Shahrom Tengku; Ahmad, Anisa (International Journal of Public Health Science (IJPHS), 2024)
In the era of digitalisation, working parents today rely more than ever on electronic gadgets as digital babysitters and device-led playtime to entertain their children. The study suggests that parents and their interactions with the home environment may contribute to shaping children’s screen time. However, many struggle to keep up with the immense variety of mobile applications easily downloaded online. Thus, long screen time exposure inhibits children’s ability to engage actively in physical activities as well as affects children’s well-being development. This scoping review aims to identify parental perceptions of children’s exposure to screens for a long period of time and how screen time affects children’s well-being. Five databases, including Scopus, Web of Science (WOS), Bielefeld Academic Search Engine (BASE), Education Resources Information Center (ERIC), and ScienceDirect, were used in this research. In the initial identification stage, 218 articles were identified from the mentioned databases above. However, there were only 81 articles found to be assessed for eligibility. A total of 34 articles are eligible for analysis and reference after the exclusion and inclusion process for data collection. The findings show that the increased exposure to screens raised concerns about potential negative effects on children’s emotions and behaviour.